Study of water pollution parameters in the dry and rainy seasons on the pollution index of the Mesuji River, Lampung, Indonesia - Abu Rosid Istomi; Suharso; Buhani; Tugiyono; Heri Satria; Emi Artika; Annisaa Siti Zulaicha (Results in Chemistry)
Background: The Mesuji River is a vital natural water resource, yet increasing human activities have resulted in significant pollution through chemical, physical, and biological contamination. This study aimed to assess the water quality of the Mesuji River by analyzing key variables: TSS (Total Suspended Solids), pH, BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), DO (Dissolved Oxygen), phosphate, fecal coliform, total coliform, and heavy metals. Methods: Between September 2022 and February 2023, water samples were collected from seven stations along the Mesuji River in Lampung Province, including Keagungan Dalam Village (MS-01), Sri Tanjung Village (MS-02), Badak Village (MS-03), Wiralaga II Village (MS-04), Gajah Mati Village (MS-05), Gebang River (MS-06), and the confluence of the Gebang and Mesuji Rivers (MS-07). Water quality variables were measured using standard methods and analyzed with descriptive statistics. Results: Mean values for TSS ranged from 3.71 ± 3.15 to 4.60 ± 2.51 mg/L, pH from 4.16 ± 0.20 to 4.22 ± 0.17, BOD from 2.30 ± 0.76 to 7.53 ± 1.96 mg/L, COD from 7.60 ± 4.30 to 34.19 ± 9.49 mg/L, and DO from 3.27 ± 0.42 to 3.33 ± 0.78 mg/L. Phosphate levels were between 0.25 ± 0.11 and 0.47 ± 0.45 mg/L, while fecal coliform and total coliform ranged from 12.91 ± 4.22 to 22.97 ± 30.94 NPM/100 mL and 16.74 ± 6.61 to 25.43 ± 11.73 NPM/100 mL, respectively. Heavy metals were detected at concentrations between (4 × 10−4) ± (5 × 10−4) mg/L and 0.02 ± (8 × 10−4) mg/L. The water quality index (WQI) indicated poor quality during the dry season (WQI = 30) and moderate quality in the rainy season (WQI = 50). Conclusions: While most stations met COD and DO standards during the rainy season, only one met these standards in the dry season. pH levels failed to meet standards in both seasons, and phosphate levels varied. The pollution index classified the river as polluted in the dry season and lightly polluted in the rainy season, highlighting the need for effective pollution management strategies.